Noise-like pulses from all-normal dispersion ytterbium doped all-fiber oscillator with semiconductor saturable absorber. (1st June 2022) - Paul, Nitish; Singh, C P; Bhuvnesh,; Gupta, P K; Mukhopadhyay, P K; Bindra, K S
Abstract: We report generation of stable train of noise like pulses (NLPs) from all-normal dispersion ytterbium doped all-fiber unidirectional ring cavity consisting of semiconductor saturable absorber (SeSA) without any bandpass filter (BPF). NLPs are characterized by their autocorrelation traces which exhibit ∼500 fs spike riding on a broad pedestal of ∼200 ps. NLP operation is also supported by its relatively broad optical spectrum along with reasonably stable longer pulse profile on oscilloscope. Numerical simulations have also been performed in detail to study the effects of cavity parameters like the cavity length, BPF bandwidth and depth of modulation ( q 0 ) of SeSA on the evolved pulses from the cavity. The simulation results suggest that stable single clean pulse (SSCP) is generated for a certain range of cavity parameters and in the absence of BPF no SSCP is possible from the cavity if the value of q 0 is below a certain value. Under this condition either NLP or no pulse is generated in the simulation. Numerically simulated NLP in a ring cavity matches qualitatively with the experimentally obtained results for NLP. The study carried out on NLP will enrich database of pulse dynamics in modelocked oscillators and has potential application in optical coherence tomography and supercontinuum generation.